An assessment of patient's satisfaction with eye care services receiving from eye hospitals in province 2, Nepal. (2021)
Executive summary: The outline of the study has altogether four chapters. In Chapter one we discuss the importance of performance indicators, like patient satisfaction, for giving a better understanding of healthcare quality. Particularly in the context of developing countries, patient satisfaction may be one of the most impactful indicators for hospital managers. Therefore, the purpose of the present study is to assess patients' satisfaction with the quality of eye care services at eye care centers and eye hospitals of Nepal. The second chapter delineates the research methodology, including the study design, tools and techniques, sample size estimation, and data analysis plan. In this cross-sectional study, we conducted exit interviews to willing patients using a pre-validated questionnaire. The questionnaire was divided into different categories including "socioeconomic/demographic", "behavior of health provider", and "Services and facilities". Patients were asked to respond to questions using a 5-point likert scale ranging from "highly dissatisfied" to "highly satisfied" These interviews were done in 3 hospitals located in province the estimated sample size was around 1209 (including a 5% non-response value). Chapter three will provide a detail description of the results, data processing and statistical analysis. We found that out of the 1190 respondents roughly 80% were males, while 20% were females. 65% of respondents had no formal education, only 1.7% respondents reported having higher than secondary level education. In our sample population 79% of patients were form the out-patient-department, and 21% from the inpatient department. Between the hospital, Gaur eye hospital had the highest rate of neutrality or dissatisfaction with a rate of 8%, followed by hospital RM Kedia and Sagarmatha Choudhary eye hospital with 6% and 0.7% percent respectively. When asked "How long can your family survive on your main source of income?" 67.06% of survey respondents reported less than 6 months. In the outpatient department group, 95% reported being satisfied or highly satisfied overall with their experience. In the Inpatient group, this value was 93%. Our findings from the questionnaires demonstrated that a majority of survey respondents (approx. 95%) across each hospital were overall satisfied or highly satisfied with their health service. We used the chi-squared test to compare several independent variables to overall satisfaction and calculated their significance level. From the analysis it was determined that education status was significantly associated with overall satisfaction. The higher the level of education, the more likely the patient would report being satisfied or highly satisfied. Likewise, socioeconomic status, waiting time, operating hours, perception of treatment plan, cleanliness, and cost of service were additional characteristics that were statistically correlated to overall satisfaction. Interestingly our data showed that the behavior of the service providers did not play a significant role in overall satisfaction. Lastly, in the final chapter we used psychological concepts as well as marketing/business concepts to explain our data with respect to quality. The Kano model, which is a theory for product development and customer satisfaction, provides a framework to describe the relationship between quality and patient satisfaction. This helped us explain the thought process behind our patient population, and how this manifested to the observed survey results. The last chapter also discusses prominent theories that describes the psychological rationale for why people think and behave a particular way. These include the expectancy value theory and the healthcare quality theory. We provide an argument for how our data reflects the expectancy value.